Induced Pluripotent Stem Cells Derived From Two Idiopathic Azoospermia Patients Display Compromised Differentiation Potential for Primordial Germ Cell Fate - Fang, Fang; Li, Zili; Zhao, Qian; Ye, Zhen; Gu, Xiuli; Pan, Feng; Li, Honggang; Xiang, Wenpei; Xiong, Chengliang (Frontiers in Cell and Developmental Biology, 2020)
At present, the etiology of most non-obstructive azoospermia (NOA) remains unclear. In vitro generation of patient-specific induced pluripotent stem cells (iPSCs) is an effective approach for exploring the mechanisms of human disease. Here, we established iPSCs from two patients with idiopathic NOA and differentiated them into primordial germ cell-like cells (PGCLCs) in vitro. Compared with iPSCs derived from normal fertile men, the NOA patient-specific iPSCs show decreased efficiency of PGCLC formation in vitro. Particularly, the embryoids derived from NOA patient-specific iPSCs show defects in the expression of early PGC genes. The transcriptome analysis reveals the expression patterns of key human PGC genes are generally similar in PGCLCs differentiated from all iPSC lines, and the differentially expressed genes (DEGs) were enriched with gene ontology (GO) of cell cycle and apoptosis regulation. Moreover, the PGCLCs derived from NOA patient-specific iPSCs might have initiated epigenetic reprogramming at a very early stage. Thus, the NOA patient-specific iPSCs exhibit poor response to germ cell induction in vitro, which may be related to the regulation of apoptotic process. These findings provide a foundation for future research on mechanism of male infertility.